Determinants of default from full completion of vaccination among children between 12 and 23 months old in Yilmana Densa district, west Gojam zone, Ethiopia, 2019 - Mekuria, Desalegn Koyto; Hailu, Getachew; Bedimo, Melkamu; Tefera, Alemu Adela (Frontiers in Public Health, 2022)
Background: Vaccination is one of the most cost effective public health interventions to prevent children from contracting vaccine-preventable diseases. In Ethiopia, default to full completion of child immunization is high and determinants of default to full completions are not discovered deeply in this study setting. Therefore this study aimed to assess the determinants of default to full completion of vaccination among children among 12 to 23 months old in Yilmana Densa District, West Gojam North west Ethiopia. Methods: A community based unmatched case control study design was employed in Yilmana Densa district among 343 (111 cases and 232 controls) randomly selected 12 to 23 months old children. The data were collected through face to face interview by using multistage sampling method. Data were entered into Epi data version 3.1 and exported to SPSS 23 software for analysis. Descriptive followed by binary and multivariable logistic regression analysis was conducted. The statistical significance was declared at p-value of 0.05. Result: This study identified that Mothers not Attended ANC Follow up [AOR=5.55, 95%CI :( 1.789-17.217)], mothers not getting information about vaccination (AOR=8.589, 95%CI: 4.414-16.714)] and mother whose time taken to reach vaccination site is more than 39 minute were at higher risk to default from completion of vaccination (AOR=3.252, 95%CI(1.952-5.417). In addition, maternal waiting time (>45minute) for child vaccination (AOR=2.674,95% CI(1.517-4.714)) and home delivery (AOR 3.19,95%CI:(1.751-5.814) were risk factors to default child from fully completion of vaccination. Conclusion: Mothers delivered at home, mothers not attending ANC follow up, mothers didn’t get health information about vaccine, mothers taking longer time to reach vaccination site and staying longer time for child vaccination are causes of defaulting. Motivate institutional delivery services utilization is recommended. The district office should consider the distribution of vaccination site by opening of new outreach site to reduce the waiting time of mothers.